2021
DOI: 10.3390/ijms22158077
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial HSP70 Chaperone System—The Influence of Post-Translational Modifications and Involvement in Human Diseases

Abstract: Since their discovery, heat shock proteins (HSPs) have been identified in all domains of life, which demonstrates their importance and conserved functional role in maintaining protein homeostasis. Mitochondria possess several members of the major HSP sub-families that perform essential tasks for keeping the organelle in a fully functional and healthy state. In humans, the mitochondrial HSP70 chaperone system comprises a central molecular chaperone, mtHSP70 or mortalin (HSPA9), which is actively involved in sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 268 publications
(353 reference statements)
0
27
0
Order By: Relevance
“…They confirmed that neutralization of HSP70 or TLR4 and kinases inhibition avoids cardiac protection [267]. Remarkably, HSP70 is a key component of mitochondrial import, translocation and protein folding [268], which are essential functions for mitochondrial biogenesis.…”
Section: Exosomes-delivery To Protect Heart Against Reperfusion Injurymentioning
confidence: 71%
“…They confirmed that neutralization of HSP70 or TLR4 and kinases inhibition avoids cardiac protection [267]. Remarkably, HSP70 is a key component of mitochondrial import, translocation and protein folding [268], which are essential functions for mitochondrial biogenesis.…”
Section: Exosomes-delivery To Protect Heart Against Reperfusion Injurymentioning
confidence: 71%
“…Importantly, the overexpression of GRP75 (including HSPA9B or mortalin-2) is found in many human malignancies which is causally correlated with their invasive growth, metastasis spread and resistance to chemotherapy and radiotherapy [ 24 , 29 , 31 , 32 ] (see also Section 4.3 ). Tumoral GRP75 is known to contribute to the cancer stemness and EMT program that are associated with the aggressiveness and persistence of mammary gland carcinomas [ 29 , 33 , 34 ].…”
Section: Members Of Hsp70 Subfamily: General Characteristics Localization Functioningmentioning
confidence: 99%
“…Exciting new roles for chaperones and co-chaperones related to inflammation, autoimmune disorders, and the previously described diseases include mitochondrial and nuclear shuttling of cargo and chaperone activity within these organelles (Figure 1). We encourage the reader to consider several reviews that cover chaperone-organelle specific activities and their role in disease in greater detail [48][49][50][51][52][53][54][55][56].…”
Section: Autoimmune Disordersmentioning
confidence: 99%